Oral health knowledge and its correlation with the oral hygiene of University of the Philippines College of Dentistry Students S.Y. 2016-2017 - Brojan, Maria Cziara G.; Garcia, Shara Mae C.; Lara, Maria Teresita C.; Alfaro, Arlene Cecilia A. (Manila Department of Community Dentistry, University of the Philippines Manila, 2017)
Introduction: Dental caries and periodontal diseases have always been a major public health issue here in the Philippines. This poor oral health condition in the country underscores the importance of the role of Filipino dentists in educating their patients on oral health promotion and maintenance. It is not enough to possess knowledge and verbally transmit the information. Their personal belief and practices are important because as future health providers, these will potentially influence how they motivate their patients towards improved oral hygiene. It was the aim of this study to determine if there is a correlation between oral health knowledge & oral hygiene.
Methods: The study was performed at the University of the Philippines Manila, College of Dentistry. 184 students from different year levels responded to HU-DBI questionnaires. The HUDBI is used to examine the oral health-related attitudes and behavior of dental students in different countries. Thereafter, an oral examination was done to measure their Gingival and Plaque Indices. The data gathered was subjected to statistical analysis
Results: The results showed that a marked improvement in the oral health knowledge of the students as they progressed in the dental curriculum as determined by their HU-DBI scores. Likewise, the 3rd and 4th year dentistry proper and resident clinicians were shown to have better periodontal health compared to the younger students. Data analysis showed a positive correlation both between the level of dental training and the oral hygiene, and the oral health knowledge and oral health status of UPCD students.
Conclusion: The UPCD students oral knowledge and oral hygiene improved as they progressed through the academic years
Keywords: Dental hygiene; Teeth--care and hygiene; Oral hygiene; Oral health